Unpacking all-inclusive superordinate categories: Comparing correlates and consequences of global citizenship and human identities - Carmona, Margarida; Guerra, Rita; Dovidio, John F.; Hofhuis, Joep; Sindic, Denis (Frontiers in Psychology, 2022)
Previous research suggests that all-inclusive superordinate categories, such as “citizens of the world” and “humans,” may represent different socio-psychological realities. Yet it remains unclear whether the use of different categories may account for different psychological processes and attitudinal or behavioral outcomes. Two studies extended previous research by comparing how these categories are cognitively represented, and their impact on intergroup helping from host communities towards migrants. In a correlational study, 168 nationals from 25 countries perceived the group of migrants as more prototypical of the superordinate category "citizens of the world" than their national group (relative outgroup prototypicality); whereas no differences in prototypicality occurred for the category "humans". Identification with "citizens of the world" was positively associated with a disposition to oppose helping migrants and to offer dependency-oriented help. However, identification with "humans" was positively associated with helping in general, and with offering dependency- and autonomy-oriented help; and negatively associated with opposition to helping. The experimental study manipulated the salience of “citizens of the world” vs. “humans” vs. control category, among 224 nationals from 36 countries. Results showed that the salience of “humans” (vs. “citizens of the world”) triggered higher entitativity and essentialist perceptions, and dual-identity representations. No differences due to salience were found for representations of relative ingroup prototypicality or helping responses. Overall, these findings suggest that the interchangeable use of different labels is problematic, considering these might activate different representations, and thus are likely to lead, in some circumstances, to different attitudinal or behavioral outcomes.